Uganda : Technical Assistance Report-Technical Assistance Report-Report on the National Accounts Statistics Mission. (IMF Staff Country Reports; Country Report ;, 2017)
This Technical Assistance Report discusses technical advice and recommendations given by the IMF mission to the authorities of Uganda about developing the estimates of GDP for expenditure components. The previous work undertaken to develop the methodology and a compilation system for producing estimates of GDP based on expenditure components was reviewed. The IMF mission established a systematic basis for estimating household final consumption expenditures based on a constant price Commodity Flow Model (CFM). Together with the local counterpart staff, the IMF mission also developed a Microsoft Excel framework for producing the CFM. Whenever possible, links to existing workbooks were established, including those used to estimate gross output and intermediate consumption from GDP based on the production approach system.